Multi-drug Resistant Mannheimia hemolytica and Pasteurella multocida in Pneumonic Sheep in Bangladesh - Akhter, Sonia; Zihadi, Md Asief Hossain; Rahman, Md Habibur; Rahman, Md Zillur (Bangladesh Journal of Infectious Diseases, 2023)
Background: Pneumonia in sheep is a complicated multicausal disease which affects the respiratory system causing increased morbidity and herd mortality rate. The members of Pasteurellaceae family are one of the prime causes of bacterial pneumonia in ruminants. Once infected by these organisms, antimicrobial therapy becomes obligatory. In Bangladesh, causation of pneumonic pasteurellosis and their antibiogram is unknown in sheep which insists the veterinarians to choose empirical antimicrobial therapy. Objectives: This study was undertaken to identify multidrug resistant Pasteurella multocida and Mannheimia hemolytica in sheep suspected with pneumonia. Methodology: The samples of nasal swab and the lungs were collected aseptically. After overnight incubation in Brain Heart Infusion broth, the samples were streaked onto 5.0% sheep Blood Agar to obtain pure colony with characteristic features which were subjected to biochemical tests, polymerase chain reaction (PCR), and antibiogram study against eight antibiotics. Results: A total number of 140 samples were collected of which 120 nasal swabs and 20 lungs were collected aseptically. In total, 16.7% pneumonia cases in sheep were found to be caused by Pasteurella species. Out of 140 samples, 43.57% (61/140) were positive for Mannheimia hemolytica (68.85%) and 19.67% for Pasteurella multocida. The mixed infection by both organisms was 11.48%. The Mannheimia hemolytica (MH) was predominant in lungs (100.0%) and nasal swab samples (18.3%) than Pasteurella multocida (PM) which were 15% and 7.5% respectively. All the isolates were found to be multi-drug resistant where resistance against Penicillin and Ampicillin was 100% for all isolates. The resistance of Mannheimia hemolytica and Pasteurella multocida towards sulfonamide, ceftriaxone, oxytetracycline, gentamicin, and streptomycin were 63.33%, 49.44%, 44.44%. 16.67%, 11.11% and 78.22%, 45.46%, 45.45%, 36.36%, 27.27% respectively. Among all antibiotics tested, Chloramphenicol stands out to be the most effective one (100% sensitive). Conclusion: This study states the first molecular identification of Mannheimia hemolytica and Pasteurella multocida from sheep suspected with pneumonia in Bangladesh and their antibiogram pattern against commonly prescribed antimicrobials. Due to their commensalism nature and wide host coverage, these MDR pathogens warrant judicious use of antibiotics in small ruminants to reduce veterinary public health hazard. Bangladesh Journal of Infectious Diseases, June 2023;10(1):16-23